Implementation of The Discovery Inquiry Learning Strategy to Read and Write The Qur'an for Children with Special Needs - Widiastuti, Widiastuti; Salahuddin, Rahmad; Astutik, Anita Puji (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
One of the institutions for students with special needs that utilizes the strategy of discovery inquiry learning in Quranic literacy education is Lentera Fajar Indonesia Integrated Learning Center (PKBM), located in Sidoarjo City, East Java. This research aims to determine the discovery inquiry learning strategies used by institutions for children with special needs in Quranic literacy education. The research method employed is qualitative descriptive, which aims to describe and elaborate on the implementation of discovery inquiry learning strategies in Quranic literacy education. In the findings of this research, there are three categories of classification for children with special needs in terms of their levels, namely advanced and basic levels, utilizing guided discovery inquiry strategy. Meanwhile, the intermediate level utilizes the modified free discovery inquiry strategy. Teaching aids such as flashcards, Iqra' books, and techniques involving repeated imitation of sounds, along with initial stimuli in Quranic literacy education, as well as training students' motor skills through tracing Hijaiyah worksheets, are effectively employed by teachers to enhance student achievement in the learning materials. This effectiveness is evident from the evaluation results conducted every semester, assessing student progress through assessment forms and reports provided by the responsible teacher to the students' parents. Despite the inhibiting factors that affect the success of this strategy, such as students' low academic abilities, lack of parental support, and inconsistency in maintaining the established routines.